1998
DOI: 10.1128/aem.64.9.3496-3498.1998
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Ruminal Bacteria Protect Sheep from Fluoroacetate Poisoning

Abstract: Four strains of Butyrivibrio fibrisolvens, transformed with a gene encoding fluoroacetate dehalogenase, maintained a combined population of 106 to 107 cells ml−1 in the rumens of test sheep. Five inoculated sheep showed markedly reduced toxicological symptoms after fluoroacetate poisoning when behavioral, physiological, and histological effects were compared with those of five uninoculated control sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 9 publications
3
44
0
1
Order By: Relevance
“…Globally, fluoroacetate is found in over 40 plant species (Baron et al, 1987;Harper et al, 2003) and is responsible for the intoxication of commercial livestock species (Aplin & Cannon, 1971;Nwude & Parsons, 1977;McIlroy, 1982). Owing to this problem associated with fluoroacetate-accumulating plants, dehalogenase genes have also FEMS Microbiol Ecol 80 (2012) 671-684 ª 2012 Commonwealth of Australia MICROBIOLOGY ECOLOGY been used to develop transgenic rumen bacteria (Gregg et al, 1994) which detoxify fluoroacetate within the gastrointestinal tract of ruminant livestock (Gregg et al, 1998;Padmanabha et al, 2004). The use of dehalogenases and other microbial enzymes has also been proposed for bioremediation of contaminated soil and water (Loffler & Edwards, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, fluoroacetate is found in over 40 plant species (Baron et al, 1987;Harper et al, 2003) and is responsible for the intoxication of commercial livestock species (Aplin & Cannon, 1971;Nwude & Parsons, 1977;McIlroy, 1982). Owing to this problem associated with fluoroacetate-accumulating plants, dehalogenase genes have also FEMS Microbiol Ecol 80 (2012) 671-684 ª 2012 Commonwealth of Australia MICROBIOLOGY ECOLOGY been used to develop transgenic rumen bacteria (Gregg et al, 1994) which detoxify fluoroacetate within the gastrointestinal tract of ruminant livestock (Gregg et al, 1998;Padmanabha et al, 2004). The use of dehalogenases and other microbial enzymes has also been proposed for bioremediation of contaminated soil and water (Loffler & Edwards, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mono£uoroacetate is found in various pasture plants at levels of up to 5 g kg 31 [194] and has an LD 50 in ruminants of approximately 0.3 mg kg 31 of body weight. Gregg et al [143] inoculated four strains of recombinant B. ¢brisolvens, transformed with a gene encoding £uoroacetate dehalogenase into sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have released bacteria into the rumen and have generally found that organisms disappeared within a few hours (Attwood et al 1988;Miyagi et al 1996;Gregg et al 1998). In contrast, it was possible here to detect xynA in the rumen for more than 20 days with highly speci®c PCR primers.…”
Section: Discussionmentioning
confidence: 80%